An Analysis of Factors Influencing the Millennial Stock Community's Interest in Investing in the Capital Market - Ningsih, Putu Tirta Sari; Muhammad Gusvarizon; Nurlita Indah (Ilmu Ekonomi Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of investment benefits, motivation, and education on the interest of millennial community members to invest in the capital market The research methodology used is a quantitative methodology with cross section data and primary data obtained from the distribution of questionnaires. The sampling technique used purposive sampling method with data in 2022 as many as 100 samples. The data analysis technique used is multiple linear regression by conducting validity tests, reliability tests, partial and simultaneous hypothesis testing. To test the effect of significance with a significant level of 5% The results of this study indicate that partially the variables of Investment Benefits, Motivation, Return, and Education, have a significant positive correlation coefficient value on the investment interest of the millennial stock community to invest in the capital market. Simultaneously the independent variables of investment benefits, motivation, returns, have a significant relationship to the educational variable, namely the investment interest of the millennial stock community to invest in the capital market. The coefficient of determination shows a figure of 51.1% that the free variation of investment benefits, motivation, return, education is able to explain the ups and downs of the variables affecting the investment interest of the millennial community to invest in the capital market 51.1% while the remaining 48.9% is influenced by variables other free.